2022
DOI: 10.1088/1361-6463/ac8081
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet and visible photo-response of transparent conductive Al-doped ZnO (AZO)/n-Silicon isotype heterojunction device

Abstract: In this work, the electrical and photoresponse measurements of a transparent conductive Al-doped ZnO (AZO)/n-Si heterojunction device were conducted in visible light and UV wavelengths. AZO film was deposited by sputtering onto an n-Si wafer and investigated by means of morphological, chemical and electrical characterizations. The AZO/n-Si rectifying device exhibits an excellent reproducibility without noticeable variations after 90 days of measurements. At self-powered mode, the maximum on/off ratios were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Although the changes at different voltages show similar behavior to each other, it is seen that the increase in photocurrent is low with increasing light intensities up to 40 mW and then increases rapidly after 40 mW. This nonlinear variation, that is, the low photocurrent at low light intensities, was attributed to the recombination of electrons and holes [59][60][61] and also to the presence of traps between the Ag@ZnO/p-Si interface. In other words, at high light intensities, recombination is thought to decrease and traps are de-trapped, thereby increasing the photocurrent.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Although the changes at different voltages show similar behavior to each other, it is seen that the increase in photocurrent is low with increasing light intensities up to 40 mW and then increases rapidly after 40 mW. This nonlinear variation, that is, the low photocurrent at low light intensities, was attributed to the recombination of electrons and holes [59][60][61] and also to the presence of traps between the Ag@ZnO/p-Si interface. In other words, at high light intensities, recombination is thought to decrease and traps are de-trapped, thereby increasing the photocurrent.…”
Section: Resultsmentioning
confidence: 70%
“…The EQE of an optical device is the parameter that helps to analyze the efficiency of the photodetector in converting the incoming photonic signal into an electrical signal 59 . EQE‐ V plots were obtained (Figure 8D) using the parameters obtained from the I – V characteristics under UV light as a function of light intensity with the help of the following equation 63,82 : rmEQEbadbreak=false(IlightIdarkfalse)/qP/hv$$\begin{equation}{rm{EQE}} = \frac{( I_{\mathrm{light}} - I_{\mathrm{dark}})/q}{P /hv}\end{equation}$$where h is the Planck constant, and ν is the incident light frequency…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chatzigiannakis et al have recently reported only photocurrent spectra of an ALD grown ZnO/Si n-n isotype heterojunction photodetector. Similarly, a few other reports are also available, but detailed investigation and analyses such as photocurrent transients, photosensitivity, response time, stability, low power detectability, and photoresponse under frequency-modulated illuminations have not been performed to show the ZnO/Si isotype junction as a high-performance broadband photodetector.…”
Section: Introductionmentioning
confidence: 99%